Investigation of thrombin generation assay to predict vaso-occlusive crisis in adulthood with sickle cell disease - Feugray, Guillaume; Kasonga, Fiston; Grall, Maximilien; Dumesnil, Cécile; Benhamou, Ygal; Brunel, Valery; Le Cam Duchez, Véronique; Lahary, Agnès; Billoir, Paul (Frontiers in Cardiovascular Medicine, 2022)
Introduction Sickle cell disease (SCD) is an inherited haemoglobinopathy disorder. The main consequence is synthesis of haemoglobin S leading to chronic haemolysis associated with morbidity. The aim of this study was to investigate Thrombin Generation Assay (TGA) to assess hypercoagulability in SCD and TGA parameters as biomarkers of vaso-occlusive crisis (VOC). Materials/methods We performed TGA in platelet poor plasma with 1pM of tissue factor and 4µM of phospholipid-standardized concentration. We measured soluble thrombomodulin, soluble endothelial Protein C Receptor and Tissue Factor Pathway Inhibitor. Experiments were done in duplicate for patients and controls. Results A total of 113 patients with SCD, 83 at steady state and 30 during VOC, and 25 controls were included. Among the 83 patients at steady state, 37 were S/S-1 S/β0, 20 were S/Sα3.7 and 19 were S/C-7 S/β+; 28 developed a VOC in the following year (median: 4 months [2.25-6]). We observed an increase of peak and velocity associated with a reduction of lagtime and time to peak and no difference of endogenous thrombin potential (ETP) in patients compared to controls. Decreases of physiological anticoagulants were also observed. TGA confirmed prothrombotic state in all SCD genotypes or clinical status. The association of ETP>1207 nM.min and peak>228.5 nM presented a sensitivity of 73.5% and a specificity of 93.9% to predict VOC development in the following year. Conclusion We have demonstrated a hypercoagulable state in SCD induced by chronic haemolysis. ETP and peak could be used to predict VOC development and to initiate new therapeutics in SCD.